Skin picking: The view from dermatology - Rungsima Wanitphakdeedecha (2018)
© Cambridge University Press 2010. Introduction The psychocutaneous disorders span a vast range of entities from primary skin conditions known to have psychologic sequelae (e.g., psoriasis, pemphigus, alopecia, acne vulgaris) to psychological or psychiatric conditions resulting in severe skin morbidity (Folks and Warnock 2001). The psychiatric conditions with skin manifestations are difficult to diagnose and are often misdiagnosed. Commonly, these “psychodermatoses” are grouped into one broad category generally known as “psychogenic excoriation” (O’sullivan et al. 1999). This designation conflicts with the proper identification of psychiatric disorders from which the patient may suffer and limits the extent and proper selection of required treatment modalities. Psychogenic excoriation (also referred to as neurotic excoriation, compulsive skin picking, dermatotillomania, and acne excoriée) is characterized by excessive picking and scratching of normal skin or skin with minimal surface texture irregularities (Arnold, Auchenbach, and McElroy 2001). This condition affects up to 2% of patients in dermatology clinics and leads to marked functional disability, further emotional distress, and medical complications (e.g., infections, limb loss, severe bleeding). Individuals suffering from psychogenic excoriation report significant distress and psychosocial impairment, including occupational and marital difficulties (Folks and Warnock 2001). This condition has received special attention from pediatricians and mental health professionals because of the underlying presence of obsessive-compulsive personality and body dysmorphic disorders affecting many patients with severe excoriations (Arnold et al. 1998; Bach and Bach 1993; Deckersbach et al. 2002; Gupta, Gupta, and Schork 1996; Koo and Smith 1991a, 1991b; Wilhelm et al. 1999).